2016
DOI: 10.1097/hjh.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities in patients with hypertension – a study of registered diagnoses 2009–2013 in the total population in Stockholm County, Sweden

Abstract: Increased awareness of the risk of depression and anxiety among hypertensive patients is needed to combat hypertension, its complications, and psychiatric suffering in the population. Hypertension is probably underdiagnosed and neglected in individuals with severe psychiatric disorders. We warrant efforts to integrate psychiatric and hypertensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 54 publications
2
32
0
8
Order By: Relevance
“…The relationship between mental illness and various medical conditions has been widely described in literature. There is evidence of increased mental disorders among patients suffering from infectious diseases like tuberculosis, HIV and also among non-communicable diseases like diabetes, hypertension and cancer [1923]. Further, it has also been shown that persons suffering from mental disorders have a greater burden of chronic medical conditions than the general population [24].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between mental illness and various medical conditions has been widely described in literature. There is evidence of increased mental disorders among patients suffering from infectious diseases like tuberculosis, HIV and also among non-communicable diseases like diabetes, hypertension and cancer [1923]. Further, it has also been shown that persons suffering from mental disorders have a greater burden of chronic medical conditions than the general population [24].…”
Section: Discussionmentioning
confidence: 99%
“…With more and more younger and middle-age adults moving to the cities for work, there is an increasing need for mental health care for older adults remaining in rural regions. Although it is well recognized that psychiatric comorbidity, especially depression, has a negative long-term impact on health outcomes for older adults with hypertension (HTN) (Adamenko, 1967; Musselman et al ., 1998; Sandstrom et al ., 2016; Smith et al ., 2013), to date, few studies have explored the relationship between depression and HTN in rural China.…”
Section: Introductionmentioning
confidence: 99%
“…17,33 In this context, this study demonstrated that there was an association between these disorders and SAH, as reported in the available literature. 17,[34][35][36] However, it cannot be concluded whether SAH is one of the causes of these disorders in vulnerable patients, whether it is an aggravating factor, whether these disorders predispose patients to developing SAH, or whether there is actually a bidirectional relationship. 1,9,15,[17][18][19]35,36 Another point that it is indispensable to discuss is that both anxiety and depression are risk factors for CVD, such as AMI, stroke, and PAD.…”
Section: Discussionmentioning
confidence: 99%